Complete Genome Sequence of Photobacterium damselae Subsp. damselae Strain SSPD1601 Isolated from Deep-Sea Cage-Cultured Sebastes schlegelii with Septic Skin Ulcer - Yongxiang Yu; Zheng Zhang; Yingeng Wang; Meijie Liao; Xiaojun Rong; Bin Li; Kai Wang; Jing Chen; Hao Zhang (International Journal of Genomics)
Photobacterium damselae subsp. damselae (PDD) is a Gram-negative bacterium that can infect a variety of aquatic organisms and humans. Based on an epidemiological investigation conducted over the past 3 years, PDD is one of the most important pathogens causing septic skin ulcer in deep-sea cage-cultured Sebastes schlegelii in the Huang-Bohai Sea area and present throughout the year with high abundance. To further understand the pathogenicity of this species, the pathogenic properties and genome of PDD strain SSPD1601 were analyzed. The results revealed that PDD strain SSPD1601 is a rod-shaped cell with a single polar flagellum, and the clinical symptoms were replicated during artificial infection. The SSPD1601 genome consists of two chromosomes and two plasmids, totaling 4,252,294 bp with 3,751 coding sequences (CDSs), 196 tRNA genes, and 47 rRNA genes. Common virulence factors including flagellin, Fur, RstB, hcpA, OMPs, htpB-Hsp60, VasK, and vgrG were found in strain SSPD1601. Furthermore, SSPD1601 is a pPHDD1-negative strain containing the hemolysin gene hlyAch and three putative hemolysins (emrA, yoaF, and VPA0226), which are likely responsible for the pathogenicity of SSPD1601. The phylogenetic analysis revealed SSPD1601 to be most closely related to Phdp Wu-1. In addition, the antibiotic resistance phenotype indicated that SSPD1601 was not sensitive to ceftazidime, pipemidic, streptomycin, cefalexin, bacitracin, cefoperazone sodium, acetylspiramycin, clarithromycin, amikacin, gentamycin, kanamycin, oxacillin, ampicillin, and trimethoprim-sulfamethoxazole, but only the bacitracin resistance gene bacA was detected based on Antibiotic Resistance Genes Database. These results expand our understanding of PDD, setting the stage for further studies of its pathogenesis and disease prevention.